Halogen-free flame-retardant cable material and preparation method thereof

CN122878660APending Publication Date: 2026-10-09LUOYANG YICIAN ELECTRIC CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611390317.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]本发明旨在至少解决现有技术中存在阻燃性能和拉伸强度欠佳的技术问题之一

Benefits of technology

(1)本发明选用本身不燃的埃洛石纳米管作为阻燃基料,将哌嗪与3-氯丙基三甲氧基硅烷形成同时具备硅氧锚固结构与阻燃功能的哌嗪硅烷对埃洛石纳米进行改性,有效改善了埃洛石纳米管在基体中的分散性并能在燃烧过程中均匀地释放阻燃气体;此外,还加入了苯酚钠分散液与聚二氯磷腈发生亲核取代引入苯氧基,使得在燃烧过程中体系能形成更加致密和连续的炭层,同时,苯氧基的引入还能改善苯氧基化聚磷腈的刚性,而加入的1,4-双(羟基二甲基硅烷基)苯则通过其含有的硅羟基接入聚二氯磷腈,引入刚性亚苯基与硅元素,有效增强了高温下炭层的热稳定性与成炭效率;并且,本发明制得的改性埃洛石纳米管不含卤元素,将其作为填料加入体系能有效增强制得电缆料的阻燃效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878660A_ABST
    Figure CN122878660A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of cable material, especially to a halogen-free flame-retardant cable material and a preparation method thereof, the cable material comprises the following raw materials: ethylene-vinyl acetate copolymer, linear low-density polyethylene, modified halloysite nanotube, SEBS-g-MAH, p-acetoxystyrene, dicumyl peroxide, antioxidant 1010, antioxidant 168, zinc stearate and PE wax, the ethylene-vinyl acetate copolymer and the linear low-density polyethylene are used as the resin matrix of the system, the halloysite nanotube modified by piperazine silane and phenoxy polyphosphazene is used as the halogen-free flame-retardant filler to provide the flame-retardant performance of the system, meanwhile, the SEBS-g-MAH and the p-acetoxystyrene are used as the matrix modifier, and the antioxidant 1010, the antioxidant 168, the zinc stearate and the PE wax are used to prepare the cable material, the cable material prepared by the formula and the preparation method has high flame-retardant performance and tensile strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of cable material technology, and in particular relates to a halogen-free flame-retardant cable material and its preparation method. Background Technology

[0002] With increasing societal emphasis on fire safety, the requirements for the flame-retardant performance of wires and cables are becoming increasingly stringent. Traditional halogen-containing flame-retardant cable materials produce large amounts of toxic fumes and corrosive gases during combustion, easily hindering escape and rescue efforts and damaging the environment and electronic equipment. They are gradually failing to meet market and safety regulations. Halogen-free flame-retardant cable materials, due to their low smoke density and minimal release of toxic and harmful gases during combustion, have become a key research focus in the industry. Currently, commonly used halogen-free flame-retardant cable materials often employ inorganic hydroxides such as aluminum hydroxide and magnesium hydroxide as flame-retardant fillers. These fillers require significant addition to achieve the desired flame-retardant effect; excessive addition severely damages the mechanical properties of the cable matrix, leading to a decrease in tensile strength, elongation at break, and other indicators, affecting the cable's processing performance and service life. Existing nano-filler-modified flame-retardant solutions suffer from poor compatibility between the flame-retardant components and the matrix resin, and low utilization rates of flame-retardant elements. They cannot consistently achieve high flame-retardant effects while maintaining good mechanical properties, making it difficult to meet the high-performance requirements of low-voltage power distribution, rail transportation, and other fields.

[0003] Patent application CN118931017B discloses a halogen-free flame-retardant polyolefin cable material and its preparation method, belonging to the field of cable material technology. This halogen-free flame-retardant polyolefin cable material comprises the following raw materials in parts by weight: 40-50 parts ethylene-vinyl acetate copolymer, 60-70 parts high-density polyethylene, 15-25 parts low-density polyethylene, 8-10 parts flame retardant, 7-9 parts inorganic filler, 0.8-1 part antioxidant, 0.8-1 part ultraviolet absorber, 0.5-1 part lubricant, 0.5-1 part dispersant, and 0.02-0.04 parts initiator. The halogen-free flame-retardant elements nitrogen, phosphorus, and silicon in the flame retardant synergistically enhance flame retardancy, and the flame retardant and inorganic filler work together to impart highly efficient and safe smoke suppression and flame retardancy to the cable material. The flame retardant and inorganic filler are uniformly dispersed in the matrix material and have good compatibility with other raw materials, allowing each raw material to fully exert its corresponding effect, giving the cable material excellent smoke suppression, flame retardancy, oxidation resistance, and toughness. In the formulation of this patent application, the filling amount of flame retardant and filler is low, which can only meet the basic flame retardancy requirements and is difficult to adapt to high flame retardancy and fire resistance scenarios. The system relies on high-density polyethylene to ensure tensile strength, and the mechanical properties are acceptable, but the flame retardant component cannot reinforce it. Increasing the amount of flame retardant material will lead to a decrease in strength, and it is difficult to improve the strength of both at the same time.

[0004] Therefore, developing a halogen-free flame-retardant cable material that combines excellent flame-retardant properties with good tensile strength is of great practical significance. Summary of the Invention

[0005] This invention aims to at least solve one of the technical problems of insufficient flame retardant properties and tensile strength in existing technologies. To this end, this invention proposes a halogen-free flame-retardant cable material and its preparation method.

[0006] To achieve the above objectives, the present invention provides a halogen-free flame-retardant cable material, comprising, by weight, the following parts of raw materials: 55-60 parts of ethylene-vinyl acetate copolymer, 40-45 parts of linear low-density polyethylene, 25-30 parts of modified halloysite nanotubes, 5-6 parts of SEBS-g-MAH, 2-3 parts of p-acetoxystyrene, 2-2.5 parts of dicumyl peroxide, 0.2-0.3 parts of antioxidant 1010, 0.2-0.3 parts of antioxidant 168, 2-3 parts of zinc stearate, and 2-3 parts of PE wax; The modified halloysite nanotubes are prepared by modifying halloysite nanotubes with piperazine silane and phenoxylated polyphosphazene.

[0007] This invention uses ethylene-vinyl acetate copolymer and linear low-density polyethylene as the resin matrix of the system, and halloysite nanotubes modified with piperazine silane and phenoxylated polyphosphazene as halogen-free flame retardant fillers to provide flame retardant properties to the system. At the same time, SEBS-g-MAH and para-acetoxystyrene are used as matrix modifiers, and antioxidant 1010, antioxidant 168, zinc stearate and PE wax are combined to prepare cable material. The cable material prepared under the formulation and preparation method of this invention has high flame retardant properties and tensile strength.

[0008] In some embodiments of the present invention, the specific preparation method of the modified halloysite nanotubes includes the following steps: (1) Purge nitrogen gas, mix polydichlorophosphazene and anhydrous tetrahydrofuran under ice bath conditions and stir, keep ice bath conditions, add sodium phenolate dispersion and stir, then heat and stir once, then heat and stir a second time, add the mixture dropwise and stir, filter, and take the filtrate as phenoxylated polyphosphazene. (2) Add halloysite nanotubes to an ethanol aqueous solution and stir. After adjusting the pH once, add piperazine silane and stir under controlled temperature. After adjusting the pH a second time, stir again, centrifuge, filter, take filter residue A and wash to obtain piperazine silane modified intermediate material. Under nitrogen protection, take piperazine silane modified intermediate material and disperse it in tetrahydrofuran. Then add phenoxylated polyphosphazene and triethylamine and stir under controlled temperature. Centrifuge, filter, collect filter residue B, wash and dry to obtain modified halloysite nanotubes.

[0009] In some embodiments of the present invention, the polydichlorophosphazene in step (1) is 95-100 parts by weight, the anhydrous tetrahydrofuran is 900-1000 parts by weight, the sodium phenolate dispersion is 73-78 parts by weight, and the mixture is 120-128 parts by weight.

[0010] In some embodiments of the present invention, the preparation method of polydichlorophosphazene in step (1) includes the following steps: Nitrogen gas was introduced, and hexachlorotriphosphazene and 1,2,4-trichlorobenzene were mixed. Sulfamide acid was added, and the mixture was refluxed. After cooling, the mixture was poured into n-heptane, and the precipitate was washed to obtain polydichlorophosphazene.

[0011] Further, the hexachlorotriphosphazene is 120-125 parts by weight, 1,2,4-trichlorobenzene is 110-125 parts by weight, and sulfonamide acid is 0.13-0.16 parts by weight.

[0012] Furthermore, the hexachlorotriphosphazene has been dried under vacuum at 50-60°C for 10-12 hours; the specific steps for adding sulfamic acid and reflux are as follows: hexachlorotriphosphazene and 1,2,4-trichlorobenzene are mixed and the temperature is controlled at 190-195°C, sulfamic acid is added, and the temperature is raised to 205-210°C for reflux for 5-6 hours; the cooling temperature is 80-90°C; the washing is performed with n-heptane 2-3 times.

[0013] In some embodiments of the present invention, the preparation method of the sodium phenolate dispersion in step (1) includes the following steps: vacuum drying of sodium phenolate, dispersing the dried sodium phenolate in anhydrous tetrahydrofuran to obtain sodium phenolate dispersion; Sodium phenoxide dispersion introduces phenoxy groups through nucleophilic substitution with the active P-Cl bonds in polydichlorophosphazene. During combustion, the phenoxy groups promote the formation of a denser and more continuous char layer. Simultaneously, the phenoxy groups synergistically interact with the phosphorus and nitrogen elements in polydichlorophosphazene, accelerating the formation of a continuous and dense char layer on the combustion surface, thus effectively blocking heat and oxygen transfer. Furthermore, the introduction of phenoxy groups improves the rigidity of phenoxylated polyphosphazene. Using phenoxylated polyphosphazene to modify halloysite nanotubes effectively increases the hardness of the halloysite nanotubes, enabling them to function as rigid fillers to reinforce the tensile strength of the matrix resin in the system.

[0014] Furthermore, the vacuum drying temperature is 55-60℃, the time is 6-8h, and the mass ratio of the dried sodium phenolate to anhydrous tetrahydrofuran is 1:1.8-1.9.

[0015] In some embodiments of the present invention, the preparation method of the mixture in step (1) includes the following steps: dissolving 1,4-bis(hydroxydimethylsilyl)benzene in anhydrous tetrahydrofuran and then adding triethylamine and stirring to obtain a mixture; 1,4-Bis(hydroxydimethylsilyl)benzene introduces rigid phenylene and silicon elements through its silanol groups into polydichlorophosphine. At high temperatures, silicon can be further converted and enhance the thermal stability and oxidation resistance of the carbon layer, while phenylene further improves the carbonization efficiency. At the same time, since halloysite nanotubes are also present in the system, the silicon-oxygen structure introduced by 1,4-bis(hydroxydimethylsilyl)benzene may also form a more stable barrier layer together with the aluminol groups or silanol groups on the surface of halloysite nanotubes.

[0016] Further, the 1,4-bis(hydroxydimethylsilyl)benzene is 8-9.5 parts by weight, the anhydrous tetrahydrofuran is 100-110 parts by weight, and the triethylamine is 11-13 parts by weight.

[0017] Furthermore, the stirring time is 10-15 minutes.

[0018] In some embodiments of the present invention, the stirring time after mixing in step (1) is 20-30 min; the stirring time after adding sodium phenolate dispersion is 1-1.5 h; the first heating and stirring is specifically heating to room temperature and stirring for 2-3 h; the second heating and stirring is specifically heating to 50-60℃ and stirring for 4-5 h; the stirring temperature after adding the mixed solution is 55-65℃ and the time is 3-4 h.

[0019] In some embodiments of the present invention, the halloysite nanotubes in step (2) are 95-100 parts by weight, the ethanol aqueous solution is 950-1000 parts by weight, the piperazine silane is 18-23 parts by weight, the piperazine silane modified intermediate is 140-154 parts by weight, the tetrahydrofuran is 560-840 parts by weight, the phenoxylated polyphosphazene is 26-32 parts by weight, and the triethylamine is 5-8 parts by weight.

[0020] Furthermore, the halloysite nanotubes have been dried at 75-80°C for 12-16 hours; the volume concentration of the ethanol aqueous solution is 85%-90%.

[0021] Furthermore, the halloysite nanotubes have an average diameter of approximately 90-100 nm. Halloysite nanotubes are inorganic nanomaterials with a hollow tubular structure. Their inner surface has aluminum alcohol groups, and their outer surface has silanol groups. Halloysite nanotubes are non-flammable and have high thermal stability. After the thermal decomposition of the matrix, they can remain in the residual char layer as an inorganic support framework to improve the integrity, density, and anti-collapse ability of the char layer. At the same time, their tubular structure can extend the transfer path of heat, oxygen, and combustible pyrolysis gases, reduce the rate of heat diffusion into the material interior, and prevent combustible volatiles from being released into the combustion zone.

[0022] In some embodiments of the present invention, the method for preparing piperazine silane in step (2) includes the following steps: Under nitrogen protection, piperazine was dispersed in toluene, and 3-chloropropyltrimethoxysilane was added and stirred under controlled temperature. The mixture was then cooled, filtered, subjected to reduced pressure, washed, and dried under vacuum to obtain piperazine silane.

[0023] 3-Chloropropyltrimethoxysilane can achieve organic modification of fillers by condensing with hydroxyl groups on the surface of halloysite nanotubes through alkoxy hydrolysis, eliminating potential agglomeration defects of halloysite nanotubes, effectively improving the dispersion uniformity of halloysite nanotubes in the matrix, and avoiding the possibility of only local flame retardancy in the system; while piperazine contains two nitrogen atoms, which can thermally decompose during high-temperature combustion to release flame-retardant gases such as nitrogen and ammonia, diluting the concentration of oxygen and combustible pyrolysis products in the combustion zone and slowing down the combustion reaction rate; By reacting 3-chloropropyltrimethoxysilane with piperazine to form piperazine silane, which possesses both a silicon-oxygen anchoring structure and flame-retardant function, and then using piperazine silane to modify halloysite nanotubes, the piperazine structure can be stably grafted onto the surface of halloysite nanotubes. This not only improves the dispersibility of halloysite nanotubes in the matrix and reduces filler agglomeration, but also allows for the uniform release of flame-retardant gases during combustion. In addition, the surface-active groups in piperazine silane can also serve as sites for interaction with phenoxylated polyphosphazenes, and further form a phosphorus-nitrogen synergistic flame-retardant effect with the phosphorus element in phenoxylated polyphosphazenes, thereby greatly improving the flame-retardant performance of the system.

[0024] Further, the piperazine is 142-150 parts by weight, the toluene is 600-620 parts by weight, and the 3-chloropropyltrimethoxysilane is 90-94 parts by weight.

[0025] Furthermore, the temperature of the temperature-controlled stirring is 75-80℃, and the time is 6-8h; the cooling is cooling to room temperature; the decompression and washing are performed by removing toluene from the filter liquid and then washing with n-hexane 2-3 times; the temperature of the vacuum drying is 40-50℃, and the time is 10-12h.

[0026] In some embodiments of the present invention, the stirring time for adding the ethanol aqueous solution and stirring in step (2) is 20-30 min; the first pH adjustment is to adjust the pH to 4.0-5.0 with glacial acetic acid; the temperature for adding piperazine silane and stirring under controlled temperature is 60-70℃ for 5-6 h; the second pH adjustment and stirring is to adjust the pH to 8.0-8.5 with triethylamine and then stir for 30-60 min; the washing of filter residue A is to wash it 2-3 times with anhydrous ethanol and tetrahydrofuran respectively; the temperature for adding phenoxylated polyphosphazene and triethylamine and stirring under controlled temperature is 55-65℃ for 4-5 h; the washing of filter residue B is to wash it 2-3 times with anhydrous ethanol, deionized water and acetone respectively; and the drying is to vacuum dry at 75-80℃ for 12-18 h.

[0027] The present invention also provides a method for preparing the above-mentioned halogen-free flame-retardant cable material, comprising the following steps: Ethylene-vinyl acetate copolymer, linear low-density polyethylene, antioxidant 1010 and antioxidant 168 are premixed and then added to SEBS-g-MAH for a first mixing. After cooling, acetoxystyrene and dicumyl peroxide are added for further mixing. Modified halloysite nanotubes, zinc stearate and PE wax are added for a second mixing. The mixture is discharged, cooled and extruded to obtain the nitrified material. The nitrified material is then added to a twin-screw extruder for extrusion granulation to obtain halogen-free flame-retardant cable material.

[0028] The flexible segments in SEBS-g-MAH (styrene-ethylene-butadiene-maleic anhydride graft copolymer) exhibit good compatibility and chain entanglement with the matrix, while the hard segments provide physical support. Furthermore, the maleic anhydride groups in SEBS-g-MAH can interact with the surface groups of the modified halloysite nanotubes used as fillers, thereby forming an effective interfacial bridge between the matrix and the filler and reducing structural defects in the finished product, allowing stress to be transferred from the matrix to the filler. Meanwhile, the para-acetoxystyrene is grafted onto the molecular chain of the matrix through free radical initiation, introducing rigid benzene rings to improve the rigidity and deformation resistance of local segments, making the material less prone to molecular chain slippage during stretching. Therefore, the cable material made in this way also has high tensile strength.

[0029] In some embodiments of the present invention, the ethylene-vinyl acetate copolymer, linear low-density polyethylene, and SEBS-g-MAH are all dried at a temperature of 65-70°C for 5-6 hours.

[0030] In some embodiments of the present invention, the premixing speed is 50-70 r / min and the time is 4-5 min; the temperature of the first mixing is 175-180℃, the speed is 90-100 r / min, and the time is 4-6 min; the cooling is to cool to 160-165℃; the speed of the continued mixing is 80-90 r / min and the time is 5-6 min; the temperature of the second mixing is 165-170℃ and the time is 6-8 min. The parameters of the twin-screw extruder are as follows: Zone 1 130℃-140℃, Zone 2 140℃-150℃, Zone 3 150℃-160℃, Zone 4 160℃-170℃, Zone 5 170℃-175℃, Die head 160-165℃, and screw speed 130-150 r / min.

[0031] The beneficial effects of this invention are: (1) In this invention, halloysite nanotubes, which are non-flammable, are selected as flame-retardant base materials. Piperazine and 3-chloropropyltrimethoxysilane are used to form piperazine silane, which has both silicon-oxygen anchoring structure and flame-retardant function, to modify halloysite nanotubes. This effectively improves the dispersibility of halloysite nanotubes in the matrix and allows for the uniform release of flame-retardant gases during combustion. In addition, sodium phenolate dispersion is added to polydichlorophosphazene to introduce phenoxy groups through nucleophilic substitution. This allows the system to form a denser and more continuous char layer during combustion. At the same time, the introduction of phenoxy groups can also improve the rigidity of phenoxylated polyphosphazene. The added 1,4-bis(hydroxydimethylsilyl)benzene is introduced into polydichlorophosphazene through its silanol groups, introducing rigid phenylene and silicon elements, which effectively enhances the thermal stability and char formation efficiency of the char layer at high temperatures. Furthermore, the modified halloysite nanotubes prepared in this invention do not contain halogen elements. Adding them to the system as fillers can effectively enhance the flame-retardant effect of the prepared cable material.

[0032] (2) The SEBS-g-MAH flexible chain segments added in this invention have good compatibility with the matrix and have chain entanglement effect. At the same time, the maleic anhydride groups contained in SEBS-g-MAH can interact with the surface groups of modified halloysite nanotubes to form an interface bridge between the matrix and the filler, so that the stress can be better transferred from the matrix to the filler. The added p-acetoxystyrene effectively introduces rigid benzene rings, making it difficult for the molecular chains to slip when the material is stretched. Therefore, the cable material prepared in this way has high tensile strength. Attached Figure Description

[0033] Figure 1 FTIR images of halloysite nanotubes and modified halloysite nanotubes prepared in Example 1 of this invention; Figure 2 XPS images of halloysite nanotubes and modified halloysite nanotubes prepared in Example 1 of this invention; Figure 3NMR spectra of halloysite nanotubes and modified halloysite nanotubes prepared in Example 1 of this invention; Figure 4 This is the FTIR image of the halogen-free flame-retardant cable material prepared in Example 1 of the present invention. Detailed Implementation

[0034] The claims of the present invention will be further described in detail below with reference to specific embodiments, but this does not constitute any limitation on the present invention. Any limited modifications made by any person within the scope of protection of the claims of the present invention are still within the scope of protection of the claims of the present invention.

[0035] The ethylene-vinyl acetate copolymer used in this invention, model number: UL00628, was purchased from: Lianhong New Material Technology Co., Ltd. The linear low-density polyethylene used, model: 3021, was purchased from Huizhou Zhongli Cable Materials Co., Ltd. The purchase information for the above raw materials will not be repeated in the following content.

[0036] Preparation Example 1 In this preparation example, modified halloysite nanotubes were prepared according to the following steps: Halloysite nanotubes with an average diameter of approximately 90 nm were dried at 78 °C for 14 h for later use. Sodium phenoxide was dried under vacuum at 58 °C for 7 h. The dried sodium phenoxide was then dispersed in anhydrous tetrahydrofuran at a mass ratio of 1:1.85 to obtain a sodium phenoxide dispersion. 8.8 g of 1,4-bis(hydroxydimethylsilyl)benzene was dissolved in 105 g of anhydrous tetrahydrofuran, and 12 g of triethylamine was added and stirred for 12 min to obtain a mixture. Under nitrogen protection, 146 g of piperazine was dispersed in 610 g of toluene, and 92 g of 3-chloropropyltrimethoxysilane was added and stirred at 78 °C for 7 h. After cooling to room temperature, the mixture was filtered, and the filtrate was washed three times with n-hexane after removing toluene under reduced pressure. Then, it was dried under vacuum at 45 °C for 11 h to obtain piperazine silane.

[0037] Hexachlorotriphosphazene was vacuum dried at 55℃ for 11 hours, and nitrogen gas was purged. 122g of the dried hexachlorotriphosphazene and 118g of... 1,2,4-Trichlorobenzene was mixed, and 0.14 g of sulfonamide acid was added at 192℃. The mixture was then heated to 207℃ and refluxed for 5.5 h. After cooling to 85℃, the mixture was slowly poured into 824 g of n-heptane. The precipitate was washed twice with n-heptane to obtain polydichlorophosphazene. Nitrogen gas was purged, and 98 g of polydichlorophosphazene and 950 g of anhydrous tetrahydrofuran were mixed and stirred for 25 min under ice bath conditions. While maintaining ice bath conditions, 75 g of sodium phenolate dispersion was slowly added and stirred for 1 h. The mixture was then heated to room temperature and stirred for 2.5 h, and then heated to 55℃ and stirred for 4.5 h. 124 g of the mixture was added dropwise and stirred at 60℃ for 3.5 h. The mixture was filtered, and the filtrate was phenoxylated polyphosphazene. 98 g of dried halloysite nanotubes were added to 975 g of bulk... An 85% ethanol aqueous solution was stirred for 28 min, the pH was adjusted to 4.5 with glacial acetic acid, 20 g of piperazine silane was added, and the mixture was stirred at 65℃ for 5.5 h. The pH was adjusted to 8.2 with triethylamine, and the mixture was stirred for another 45 min. After centrifugation and filtration, the filter residue was washed three times each with anhydrous ethanol and tetrahydrofuran to obtain piperazine silane modified intermediate material. Under nitrogen protection, 147 g of piperazine silane modified intermediate material was dispersed in 700 g of tetrahydrofuran, and then 29 g of phenoxylated polyphosphazene and 6.5 g of triethylamine were added and stirred at 60℃ for 4.5 h. After centrifugation and filtration, the filter residue was collected and washed twice each with anhydrous ethanol, deionized water, and acetone. The mixture was then vacuum dried at 78℃ for 15 h to obtain modified halloysite nanotubes.

[0038] Preparation Example 2 In this preparation example, modified halloysite nanotubes were prepared according to the following steps: Halloysite nanotubes with an average diameter of approximately 100 nm were dried at 75 °C for 12 h for later use. Sodium phenolate was dried under vacuum at 55 °C for 6 h. The dried sodium phenolate was dispersed in anhydrous tetrahydrofuran at a mass ratio of 1:1.80 to obtain a sodium phenolate dispersion. 8 g of 1,4-bis(hydroxydimethylsilyl)benzene was dissolved in 100 g of anhydrous tetrahydrofuran, and 11 g of triethylamine was added and stirred for 10 min to obtain a mixed solution. Under nitrogen protection, 142 g of piperazine was dispersed in 600 g of toluene, and 90 g of 3-chloropropyltrimethoxysilane was added and stirred at 75 °C for 6 h. After cooling to room temperature, the mixture was filtered, and the filtrate was washed twice with n-hexane after removing toluene under reduced pressure. Then, it was dried under vacuum at 40 °C for 10 h to obtain piperazine silane.

[0039] Hexachlorotriphosphazene was vacuum dried at 50℃ for 10h, then purged with nitrogen. 120g of the dried hexachlorotriphosphazene and 110g of 1,2,4-trichlorobenzene were mixed, and 0.13g of sulfonamide acid was added at 190℃. The mixture was then heated to 205℃ and refluxed for 5h. After cooling to 80℃, the mixture was slowly poured into 800g of n-heptane. The precipitate was washed three times with n-heptane to obtain polydichlorophosphazene. Nitrogen was purged, and 95g of polydichlorophosphazene and 900g of anhydrous tetrahydrofuran were mixed and stirred for 20min under ice bath conditions. While maintaining the ice bath conditions, 73g of sodium phenolate dispersion was slowly added and stirred for 1h. The mixture was then heated to room temperature and stirred for 2h, then heated to 50℃ and stirred for 4h. 120g of the mixture was added dropwise and stirred at 55℃ for 3h. The mixture was filtered, and the filtrate was phenoxylated polyphosphazene. 95g of dried halloysite nanotubes were added to 950g of... An 85% ethanol aqueous solution was stirred for 25 min, and the pH was adjusted to 4.0 with glacial acetic acid. 18 g of piperazine silane was added and stirred at 60 °C for 5 h. The pH was adjusted to 8.0 with triethylamine, and stirred for another 30 min. The mixture was centrifuged and filtered. The filter residue was washed twice with anhydrous ethanol and tetrahydrofuran, respectively, to obtain piperazine silane modified intermediate material. Under nitrogen protection, 140 g of piperazine silane modified intermediate material was dispersed in 560 g of tetrahydrofuran. 26 g of phenoxylated polyphosphazene and 5 g of triethylamine were added and stirred at 55 °C for 4 h. The mixture was centrifuged and filtered, and the filter residue was collected and washed three times with anhydrous ethanol, deionized water, and acetone, respectively. The mixture was then vacuum dried at 75 °C for 12 h to obtain modified halloysite nanotubes.

[0040] Preparation Example 3 In this preparation example, modified halloysite nanotubes were prepared according to the following steps: Halloysite nanotubes with an average diameter of approximately 90 nm were dried at 80 °C for 16 h for later use. Sodium phenolate was dried under vacuum at 60 °C for 8 h. The dried sodium phenolate was dispersed in anhydrous tetrahydrofuran at a mass ratio of 1:1.90 to obtain a sodium phenolate dispersion. 9.5 g of 1,4-bis(hydroxydimethylsilyl)benzene was dissolved in 110 g of anhydrous tetrahydrofuran, and 13 g of triethylamine was added and stirred for 15 min to obtain a mixed solution. Under nitrogen protection, 150 g of piperazine was dispersed in 620 g of toluene, and 94 g of 3-chloropropyltrimethoxysilane was added and stirred at 80 °C for 8 h. After cooling to room temperature, the mixture was filtered, and the filtrate was washed three times with n-hexane after removing toluene under reduced pressure. Then, it was dried under vacuum at 50 °C for 12 h to obtain piperazine silane.

[0041] Hexachlorotriphosphazene was vacuum dried at 60℃ for 12h, then purged with nitrogen. 125g of the dried hexachlorotriphosphazene and 125g of 1,2,4-trichlorobenzene were mixed, and 0.16g of sulfonamide acid was added at 195℃. The mixture was then heated to 210℃ and refluxed for 6h. After cooling to 90℃, the mixture was slowly poured into 848g of n-heptane. The precipitate was washed twice with n-heptane to obtain polydichlorophosphazene. Nitrogen was purged, and 100g of polydichlorophosphazene and 1000g of anhydrous tetrahydrofuran were mixed and stirred for 30min under ice bath conditions. While maintaining the ice bath conditions, 78g of sodium phenolate dispersion was slowly added and stirred for 1.5h. The mixture was then heated to room temperature and stirred for 3h, then heated to 60℃ and stirred for 5h. 128g of the mixture was added dropwise and stirred at 65℃ for 4h. The mixture was filtered, and the filtrate was phenoxylated polyphosphazene. 100g of dried halloysite nanotubes were added to 1000g of... A 90% (v / v) ethanol aqueous solution was stirred for 30 min. The pH was adjusted to 5.0 with glacial acetic acid. 23 g of piperazine silane was added and stirred at 70 °C for 6 h. The pH was adjusted to 8.5 with triethylamine, and the mixture was stirred for another 60 min. The mixture was centrifuged and filtered. The filter residue was washed three times each with anhydrous ethanol and tetrahydrofuran to obtain piperazine silane modified intermediate material. Under nitrogen protection, 154 g of piperazine silane modified intermediate material was dispersed in 840 g of tetrahydrofuran. 32 g of phenoxylated polyphosphazene and 8 g of triethylamine were added and stirred at 65 °C for 5 h. The mixture was centrifuged and filtered. The filter residue was collected and washed twice each with anhydrous ethanol, deionized water, and acetone. The mixture was then vacuum dried at 80 °C for 18 h to obtain modified halloysite nanotubes.

[0042] Preparation Example 4 In this preparation example, modified halloysite nanotubes were prepared according to the following steps: Halloysite nanotubes with an average diameter of approximately 95 nm were dried at 76 °C for 13 h for later use. Sodium phenoxide was dried under vacuum at 56 °C for 6.5 h. The dried sodium phenoxide was then dispersed in anhydrous tetrahydrofuran at a mass ratio of 1:1.82 to obtain a sodium phenoxide dispersion. 8.3 g of 1,4-bis(hydroxydimethylsilyl)benzene was dissolved in 102 g of anhydrous tetrahydrofuran, and 11.5 g of triethylamine was added and stirred for 11 min to obtain a mixture. Under nitrogen protection, 144 g of piperazine was dispersed in 605 g of toluene, and 91 g of 3-chloropropyltrimethoxysilane was added and stirred at 76 °C for 6.5 h. After cooling to room temperature, the mixture was filtered, and the filtrate was washed twice with n-hexane after removing toluene under reduced pressure. Then, it was dried under vacuum at 42 °C for 10.5 h to obtain piperazine silane.

[0043] Hexachlorotriphosphazene was vacuum dried at 52℃ for 10.5h, and nitrogen was purged. 121g of the dried hexachlorotriphosphazene and 112g of 1,2,4-trichlorobenzene were mixed, and 0.14g of sulfonamide acid was added at 191℃. The mixture was then heated to 206℃ and refluxed for 5h. After cooling to 82℃, the mixture was slowly poured into 812g of n-heptane. The precipitate was washed three times with n-heptane to obtain polydichlorophosphazene. Nitrogen was purged, and 96g of polydichlorophosphazene and 920g of anhydrous tetrahydrofuran were mixed and stirred for 22min under ice bath conditions. While maintaining the ice bath conditions, 74g of sodium phenolate dispersion was slowly added and stirred for 1h. The mixture was then heated to room temperature and stirred for 2h, and then heated to 52℃ and stirred for 4h. 122g of the mixture was added dropwise and stirred at 57℃ for 3h. The mixture was filtered, and the filtrate was phenoxylated polyphosphazene. 96g of dried halloysite nanotubes were added to 960g of concentrated... A 90% ethanol aqueous solution was stirred for 26 min, and the pH was adjusted to 4.2 with glacial acetic acid. 19 g of piperazine silane was added and stirred at 62℃ for 5 h. The pH was adjusted to 8.1 with triethylamine, and the mixture was stirred for another 35 min. After centrifugation and filtration, the filter residue was washed twice with anhydrous ethanol and tetrahydrofuran, respectively, to obtain piperazine silane modified intermediate material. Under nitrogen protection, 143 g of piperazine silane modified intermediate material was dispersed in 600 g of tetrahydrofuran, and then 27 g of phenoxylated polyphosphazene and 5.8 g of triethylamine were added and stirred at 57℃ for 4 h. After centrifugation and filtration, the filter residue was collected and washed three times with anhydrous ethanol, deionized water, and acetone, respectively. The mixture was then vacuum dried at 76℃ for 13 h to obtain modified halloysite nanotubes.

[0044] Preparation Example 5 In this preparation example, modified halloysite nanotubes were prepared according to the following steps: Halloysite nanotubes with an average diameter of approximately 95 nm were dried at 77 °C for 15 h for later use. Sodium phenoxide was dried under vacuum at 59 °C for 7.5 h. The dried sodium phenoxide was then dispersed in anhydrous tetrahydrofuran at a mass ratio of 1:1.88 to obtain a sodium phenoxide dispersion. 9.1 g of 1,4-bis(hydroxydimethylsilyl)benzene was dissolved in 108 g of anhydrous tetrahydrofuran, and 12.5 g of triethylamine was added and stirred for 13 min to obtain a mixture. Under nitrogen protection, 148 g of piperazine was dispersed in 615 g of toluene, and 93 g of 3-chloropropyltrimethoxysilane was added and stirred at 79 °C for 7.5 h. After cooling to room temperature, the mixture was filtered, and the filtrate was washed three times with n-hexane after removing toluene under reduced pressure. Then, it was dried under vacuum at 48 °C for 11.5 h to obtain piperazine silane.

[0045] Hexachlorotriphosphazene was vacuum dried at 58℃ for 11.5 h, and nitrogen gas was passed through it. 124 g of the dried hexachlorotriphosphazene and 122 g of... 1,2,4-Trichlorobenzene was mixed, and 0.15 g of sulfonamide acid was added at 194 °C. The mixture was then heated to 209 °C and refluxed for 5.5 h. After cooling to 88 °C, the mixture was slowly poured into 836 g of n-heptane. The precipitate was washed twice with n-heptane to obtain polydichlorophosphazene. Nitrogen gas was purged, and 99 g of polydichlorophosphazene and 980 g of anhydrous tetrahydrofuran were mixed and stirred for 28 min under ice bath conditions. While maintaining the ice bath conditions, 77 g of sodium phenolate dispersion was slowly added and stirred for 1.5 h. The mixture was then heated to room temperature and stirred for 2.5 h, and then heated to 58 °C and stirred for 4.5 h. 126 g of the mixture was added dropwise and stirred at 63 °C for 3.5 h. The mixture was filtered, and the filtrate was phenoxylated polyphosphazene. 99 g of dried halloysite nanotubes were added to 990 g of... A 90% (v / v) ethanol aqueous solution was stirred for 29 min, and the pH was adjusted to 4.8 with glacial acetic acid. 22 g of piperazine silane was added and stirred at 68 °C for 5.5 h. The pH was adjusted to 8.4 with triethylamine, and the mixture was stirred for another 55 min. After centrifugation and filtration, the filter residue was washed three times each with anhydrous ethanol and tetrahydrofuran to obtain piperazine silane modified intermediate material. Under nitrogen protection, 151 g of piperazine silane modified intermediate material was dispersed in 780 g of tetrahydrofuran, and then 31 g of phenoxylated polyphosphazene and 7.2 g of triethylamine were added and stirred at 63 °C for 4.5 h. After centrifugation and filtration, the filter residue was collected and washed twice each with anhydrous ethanol, deionized water, and acetone. The mixture was then vacuum dried at 77 °C for 16 h to obtain modified halloysite nanotubes.

[0046] Example 1 This embodiment prepares halogen-free flame-retardant cable material using the following method: Ethylene-vinyl acetate copolymer, linear low-density polyethylene, and SEBS-g-MAH were dried at 68°C for 5.5 hours and then set aside for later use.

[0047] 57g of dried ethylene-vinyl acetate copolymer, 42g of dried linear low-density polyethylene, 0.22g of antioxidant 1010 and 0.25g of antioxidant 168 were premixed at 60r / min for 4.5min. Then, 5.2g of dried SEBS-g-MAH was added and mixed at 178℃ and 95r / min for 5min. The mixture was then cooled to 162℃, and 2.2g of p-acetoxystyrene and 2.2g of dicumyl peroxide were added and mixed at 85r / min for another 5.5min. Finally, 27g of modified halloysite nanotubes prepared in Example 1, 2.2g of zinc stearate and 2.5g of PE wax were added and mixed at 168℃ for 7min. The mixture was then discharged, cooled, and extruded to obtain the viscous compound.

[0048] The malt-free flame-retardant cable material is obtained by extruding and granulating the malt-mixed material into a twin-screw extruder with zone 135℃, zone 2 145℃, zone 3 155℃, zone 4 165℃, zone 5 172℃, die head 162℃, and screw speed 140r / min.

[0049] Example 2 This embodiment prepares halogen-free flame-retardant cable material using the following method: Ethylene-vinyl acetate copolymer, linear low-density polyethylene, and SEBS-g-MAH were dried at 65°C for 5 hours and then set aside for later use.

[0050] 55g of dried ethylene-vinyl acetate copolymer, 45g of dried linear low-density polyethylene, 0.2g of antioxidant 1010 and 0.2g of antioxidant 168 were premixed at 50r / min for 4min. Then, 5g of dried SEBS-g-MAH was added and mixed at 175℃ and 90r / min for 4min. The mixture was then cooled to 160℃, and 2g of p-acetoxystyrene and 2g of dicumyl peroxide were added and mixed at 80r / min for 5min. Finally, 25g of modified halloysite nanotubes prepared in Preparation Example 3, 2g of zinc stearate and 2g of PE wax were added and mixed at 165℃ for 6min. The mixture was then discharged, cooled and extruded to obtain the viscous compound.

[0051] The malt-free flame-retardant cable material is obtained by extruding and granulating the malt-mixed material into a twin-screw extruder with zone 130℃, zone 2 140℃, zone 3 150℃, zone 4 160℃, zone 5 170℃, die head 160℃, and screw speed 130r / min.

[0052] Example 3 This embodiment prepares halogen-free flame-retardant cable material using the following method: Ethylene-vinyl acetate copolymer, linear low-density polyethylene, and SEBS-g-MAH were dried at 70°C for 6 hours and then set aside for later use.

[0053] 60g of dried ethylene-vinyl acetate copolymer, 40g of dried linear low-density polyethylene, 0.3g of antioxidant 1010 and 0.3g of antioxidant 168 were premixed at 70r / min for 5min. Then, 6g of dried SEBS-g-MAH was added and mixed at 100r / min at 180℃ for 6min. The mixture was then cooled to 165℃, and 3g of p-acetoxystyrene and 2.5g of dicumyl peroxide were added and mixed at 90r / min for another 6min. Finally, 30g of modified halloysite nanotubes prepared in Example 2, 3g of zinc stearate and 3g of PE wax were added and mixed at 170℃ for 8min. The mixture was then discharged, cooled and extruded to obtain the viscous compound.

[0054] The malt-free flame-retardant cable material is obtained by extruding and granulating the malt-mixed material into a twin-screw extruder with zone 140℃, zone 2 150℃, zone 3 160℃, zone 4 170℃, zone 5 175℃, die head 165℃, and screw speed 150r / min.

[0055] Example 4 This embodiment prepares halogen-free flame-retardant cable material using the following method: Ethylene-vinyl acetate copolymer, linear low-density polyethylene, and SEBS-g-MAH were dried at 66°C for 5 hours and then set aside for later use.

[0056] 58g of dried ethylene-vinyl acetate copolymer, 44g of dried linear low-density polyethylene, 0.28g of antioxidant 1010 and 0.22g of antioxidant 168 were premixed at 55r / min for 4min. Then, 5.8g of dried SEBS-g-MAH was added and mixed at 176℃ and 92r / min for 4.5min. The mixture was then cooled to 161℃, and 2.8g of p-acetoxystyrene and 2.4g of dicumyl peroxide were added and mixed at 82r / min for 5min. Finally, 28g of modified halloysite nanotubes prepared in Example 5, 2.8g of zinc stearate and 2.2g of PE wax were added and mixed at 166℃ for 6.5min. The mixture was then discharged, cooled, and extruded to obtain the viscous compound.

[0057] The malt-free flame-retardant cable material is obtained by extruding and granulating the malt-mixed material into a twin-screw extruder with zone 132℃, zone 2 142℃, zone 3 152℃, zone 4 162℃, zone 5 171℃, die head 161℃, and screw speed 135r / min.

[0058] Example 5 This embodiment prepares halogen-free flame-retardant cable material using the following method: Ethylene-vinyl acetate copolymer, linear low-density polyethylene, and SEBS-g-MAH were dried at 69°C for 5.5 hours and then set aside for later use.

[0059] 59g of dried ethylene-vinyl acetate copolymer, 43g of dried linear low-density polyethylene, 0.25g of antioxidant 1010 and 0.28g of antioxidant 168 were premixed at 65r / min for 4.5min. Then, 5.5g of dried SEBS-g-MAH was added and mixed at 179℃ and 98r / min for 5.5min. The mixture was then cooled to 164℃, and 2.5g of p-acetoxystyrene and 2.3g of dicumyl peroxide were added and mixed at 88r / min for another 5.5min. Finally, 29g of modified halloysite nanotubes prepared in Example 4, 2.5g of zinc stearate and 2.8g of PE wax were added and mixed at 169℃ for 7.5min. The mixture was then discharged, cooled, and extruded to obtain the viscous compound.

[0060] The malt-free flame-retardant cable material is obtained by extruding and granulating the malt-mixed material into a twin-screw extruder with zone 138℃, zone 2 148℃, zone 3 158℃, zone 4 168℃, zone 5 174℃, die head 164℃, and screw speed 145r / min.

[0061] Comparative Example 1 Compared with Example 3, the difference is that the modified halloysite nanotubes prepared in Example 2 of Example 3 were replaced with modified halloysite nanotubes prepared without the addition of sodium phenolate dispersion, while the other operation steps and parameters remained unchanged.

[0062] Comparative Example 2 Compared with Example 3, the difference is that the modified halloysite nanotubes prepared in Example 2 of Example 3 were replaced with modified halloysite nanotubes prepared without adding the mixing liquid, while the other operation steps and parameters remained unchanged.

[0063] Comparative Example 3 Compared with Example 3, the difference is that modified halloysite nanotubes prepared without piperazine were used instead of the modified halloysite nanotubes prepared in Example 2 of Example 3, while the other operation steps and parameters remained unchanged.

[0064] Comparative Example 4 Compared with Example 3, the difference is that modified halloysite nanotubes prepared in Example 2 of Example 3 were replaced with modified halloysite nanotubes prepared without the addition of 3-chloropropyltrimethoxysilane, while the other operation steps and parameters remained unchanged.

[0065] Comparative Example 5 Compared with Example 3, the difference is that the modified halloysite nanotubes prepared in Example 2 of Example 3 were replaced with modified halloysite nanotubes prepared without the addition of piperazine silane, while the other operation steps and parameters remained unchanged.

[0066] Comparative Example 6 Compared with Example 3, the difference is that SEBS-g-MAH is not added, while the other operation steps and parameters remain unchanged.

[0067] Comparative Example 7 Compared with Example 3, the difference is that p-acetoxystyrene is not added, while the other operation steps and parameters remain unchanged.

[0068] Test Example 1 (1) The limiting oxygen index of the halogen-free flame-retardant cable materials prepared in Examples 1-5 and Comparative Examples 1-7 was tested in accordance with GB / T 2406.2-2009, and the results are shown in Table 1.

[0069] (2) The tensile strength of the halogen-free flame-retardant cable materials prepared in Examples 1-5 and Comparative Examples 1-7 were tested according to GB / T 15065-2009. The results are shown in Table 1.

[0070] Table 1

[0071] As can be seen from the data in Table 1 of Examples 1-5 and Comparative Examples 1-7, the limiting oxygen index values ​​of the embodiments of the present invention are all higher than 39%, and the tensile strength values ​​are all higher than 23 MPa, indicating that the halogen-free flame-retardant cable material prepared by the present invention has both excellent flame-retardant properties and good mechanical properties.

[0072] FTIR spectra of halloysite nanotubes and modified halloysite nanotubes are shown below. Figure 1 As shown, spectrum (a) was measured using halloysite nanotubes, and spectrum (b) was measured using modified halloysite nanotubes; compared with spectrum (a), spectrum (b) retains the characteristic absorption peak of halloysite nanotubes (3695 cm⁻¹). -1 3620cm -1 and 1030cm -1 ), and at 2930cm -1 1597cm -1 and 1242cm -1 A new absorption peak appeared nearby; among them, 2930 cm⁻¹ -1 The nearby absorption peak corresponds to the CH structure in aliphatic molecules, at 1597 cm⁻¹. -1 The nearby absorption peak corresponds to the C=C bond structure in the aromatic ring, 1242 cm⁻¹ -1 The nearby absorption peaks correspond to the P=N structure in polyphosphazene, indicating that the obtained sample retains the basic structure of halloysite nanotubes while also exhibiting related structures such as organosilicon alkyl groups, aromatic ring structures, and polyphosphazene structures.

[0073] XPS plots of halloysite nanotubes and modified halloysite nanotubes are shown below. Figure 2 As shown, spectrum (a) was measured by halloysite nanotubes, and spectrum (b) was measured by modified halloysite nanotubes. Spectrum (a) mainly shows the characteristic signals of aluminum, silicon, and oxygen elements in halloysite nanotubes; compared with spectrum (a), spectrum (b) shows a significant enhancement of the carbon element signal at 284.8 eV, and characteristic signals of nitrogen and phosphorus elements appear near 399.7 eV and 133.7 eV, respectively, indicating that the obtained sample contains nitrogen- and phosphorus-containing modified components.

[0074] NMR spectra of halloysite nanotubes and modified halloysite nanotubes are shown below. Figure 3 As shown, spectrum (a) was measured using halloysite nanotubes, and spectrum (b) was measured using modified halloysite nanotubes; comparison Figure 3As shown in spectra (a) and (b), while retaining the characteristic signal (-92 ppm) of the silicon-oxygen tetrahedral structure in halloysite nanotubes, new silicon characteristic signals appear near -51 ppm, -60 ppm, and -68 ppm, corresponding to organosilicon structures with different degrees of condensation. This indicates that the silane-modified component forms a condensed silicon structure with the halloysite nanotubes. The fact that the obtained product retains the aforementioned characteristic signals after multiple washings demonstrates that the silane-modified component has stably existed on the halloysite nanotubes.

[0075] The FTIR image of the halogen-free flame-retardant cable material prepared in Example 1 is shown below. Figure 4 As shown, at 2918cm -1 and 2850cm -1 The characteristic absorption peak of polyolefin segments appears nearby, at 1738 cm⁻¹. -1 The characteristic absorption peak of the carbonyl group appears nearby, and at 1597 cm⁻¹ -1 1463cm -1 1240cm -1 1030cm -1 and 720cm -1 A corresponding characteristic absorption peak appears nearby; among them, 1597 cm⁻¹ -1 The nearby absorption peak corresponds to the C=C bond structure in the aromatic ring, 1463 cm⁻¹ -1 The nearby absorption peak corresponds to the methylene structure in the polyolefin segment, 1240 cm⁻¹ -1 The nearby absorption peak corresponds to the P=N structure in polyphosphazene, 1030 cm⁻¹ -1 The nearby absorption peak corresponds to the Si-O structure in halloysite nanotubes, 720 cm⁻¹ -1 The nearby absorption peaks correspond to the methylene structure in the polyethylene long chain, indicating that the obtained halogen-free flame-retardant cable material contains the characteristic structures of the polymer matrix, modified halloysite nanotubes, and related modified components.

[0076] Furthermore, the limiting oxygen index data from Comparative Examples 1-5 show that the limiting oxygen index of the halogen-free flame-retardant cable material decreased significantly when sodium phenolate dispersion, mixture, piperazine, 3-chloropropyltrimethoxysilane, and piperazine silane were not added. Meanwhile, the tensile strength data from Comparative Examples 6-7 show that the tensile strength of the halogen-free flame-retardant cable material was significantly affected when SEBS-g-MAH and p-acetoxystyrene were not added.

[0077] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.

Claims

1. A halogen-free flame-retardant cable material, characterized in that, By weight, it includes the following parts of raw materials: 55-60 parts of ethylene-vinyl acetate copolymer, 40-45 parts of linear low-density polyethylene, 25-30 parts of modified halloysite nanotubes, 5-6 parts of SEBS-g-MAH, 2-3 parts of p-acetoxystyrene, 2-2.5 parts of dicumyl peroxide, 0.2-0.3 parts of antioxidant 1010, 0.2-0.3 parts of antioxidant 168, 2-3 parts of zinc stearate, and 2-3 parts of PE wax; The modified halloysite nanotubes are prepared by modifying halloysite nanotubes with piperazine silane and phenoxylated polyphosphazene.

2. The halogen-free flame-retardant cable material according to claim 1, characterized in that, The specific preparation method of the modified halloysite nanotubes includes the following steps: (1) Purge nitrogen gas, mix polydichlorophosphazene and anhydrous tetrahydrofuran under ice bath conditions and stir, keep ice bath conditions, add sodium phenolate dispersion and stir, then heat and stir once, then heat and stir a second time, add the mixture dropwise and stir, filter, and take the filtrate as phenoxylated polyphosphazene. (2) Add halloysite nanotubes to an ethanol aqueous solution and stir. After adjusting the pH once, add piperazine silane and stir under controlled temperature. After adjusting the pH a second time, stir again, centrifuge, filter, take filter residue A and wash to obtain piperazine silane modified intermediate material. Under nitrogen protection, take piperazine silane modified intermediate material and disperse it in tetrahydrofuran. Then add phenoxylated polyphosphazene and triethylamine and stir under controlled temperature. Centrifuge, filter, collect filter residue B, wash and dry to obtain modified halloysite nanotubes.

3. The halogen-free flame-retardant cable material according to claim 2, characterized in that, In step (1), the polydichlorophosphazene is 95-100 parts by weight, anhydrous tetrahydrofuran is 900-1000 parts by weight, sodium phenolate dispersion is 73-78 parts by weight, and the mixture is 120-128 parts by weight.

4. The halogen-free flame-retardant cable material according to claim 2, characterized in that, The preparation method of polydichlorophosphazene in step (1) includes the following steps: passing nitrogen gas, mixing hexachlorotriphosphazene and 1,2,4-trichlorobenzene, adding sulfamic acid, refluxing, cooling and pouring into n-heptane, taking the precipitate and washing it to obtain polydichlorophosphazene; The hexachlorotriphosphazene is 120-125 parts by weight, 1,2,4-trichlorobenzene is 110-125 parts by weight, and sulfonamide acid is 0.13-0.16 parts by weight.

5. The halogen-free flame-retardant cable material according to claim 2, characterized in that, The preparation method of sodium phenolate dispersion in step (1) includes the following steps: vacuum drying sodium phenolate, dispersing the dried sodium phenolate in anhydrous tetrahydrofuran to obtain sodium phenolate dispersion; The vacuum drying temperature is 55-60℃, the time is 6-8h, and the mass ratio of the dried sodium phenolate to anhydrous tetrahydrofuran is 1:1.8-1.

9.

6. The halogen-free flame-retardant cable material according to claim 2, characterized in that, The preparation method of the mixture in step (1) includes the following steps: dissolving 1,4-bis(hydroxydimethylsilyl)benzene in anhydrous tetrahydrofuran and then adding triethylamine and stirring to obtain the mixture; The 1,4-bis(hydroxydimethylsilyl)benzene is 8-9.5 parts by weight, the anhydrous tetrahydrofuran is 100-110 parts by weight, and the triethylamine is 11-13 parts by weight.

7. The halogen-free flame-retardant cable material according to claim 2, characterized in that, In step (2), the halloysite nanotubes are 95-100 parts by weight, the ethanol aqueous solution is 950-1000 parts by weight, the piperazine silane is 18-23 parts by weight, the piperazine silane modified intermediate is 140-154 parts by weight, the tetrahydrofuran is 560-840 parts by weight, the phenoxylated polyphosphazene is 26-32 parts by weight, and the triethylamine is 5-8 parts by weight.

8. The halogen-free flame-retardant cable material according to claim 2, characterized in that, The preparation method of piperazine silane in step (2) includes the following steps: under nitrogen protection, piperazine is dispersed in toluene, 3-chloropropyltrimethoxysilane is added and stirred under controlled temperature, cooled, filtered, reduced pressure, washed, and then dried under vacuum to obtain piperazine silane; The piperazine is 142-150 parts by weight, toluene is 600-620 parts by weight, and 3-chloropropyltrimethoxysilane is 90-94 parts by weight.

9. A method for preparing halogen-free flame-retardant cable material as described in any one of claims 1-8, characterized in that, Includes the following steps: Ethylene-vinyl acetate copolymer, linear low-density polyethylene, antioxidant 1010 and antioxidant 168 are premixed and then added to SEBS-g-MAH for a first mixing. After cooling, acetoxystyrene and dicumyl peroxide are added for further mixing. Modified halloysite nanotubes, zinc stearate and PE wax are added for a second mixing. The mixture is discharged, cooled and extruded to obtain the nitrified material. The nitrified material is then added to a twin-screw extruder for extrusion granulation to obtain halogen-free flame-retardant cable material.

10. The method for preparing halogen-free flame-retardant cable material according to claim 9, characterized in that, The premixing speed is 50-70 r / min, and the time is 4-5 min; the temperature of the first mixing is 175-180℃, the speed is 90-100 r / min, and the time is 4-6 min; the cooling is to lower the temperature to 160-165℃; the speed of the continued mixing is 80-90 r / min, and the time is 5-6 min; the temperature of the second mixing is 165-170℃, and the time is 6-8 min. The parameters of the twin-screw extruder are as follows: Zone 1 130℃-140℃, Zone 2 140℃-150℃, Zone 3 150℃-160℃, Zone 4 160℃-170℃, Zone 5 170℃-175℃, Die head 160-165℃, and screw speed 130-150 r / min.

Citation Information

Patent Citations

  • Halogen-free flame-retardant polyolefin cable material and preparation method thereof

    CN118931017B